Disulfiram Alone Functions as a Radiosensitizer for Pancreatic Cancer Both In Vitro and In Vivo - Xu, Ying; Lu, Lunjie; Luo, Judong; Wang, Lili; Zhang, Qi; Cao, Jianping; Jiao, Yang (Frontiers in Oncology, 2021)
The prognosis of pancreatic cancer remains very poor worldwide, partly due to the lack of specificity of early symptoms and innate resistance to chemo-/radiotherapy. Disulfiram (DSF), an anti-alcoholism drug widely used in the clinic, has been known for decades for its antitumor effects when simultaneously applied with copper ions, including pancreatic cancer. However, controversy still exists in the context of the antitumor effects of DSF alone in pancreatic cancer and related mechanisms, especially in its potential roles as a sensitizer for cancer radiotherapy. In the present study, we focused on whether and how DSF could facilitate ionizing radiation (IR) to eliminate pancreatic cancer. DSF alone significantly suppressed the survival of pancreatic cancer cells after exposure to IR, both in vitro and in vivo. Additionally, DSF treatment alone caused DNA double-strand breaks (DSBs) and further enhanced IR-induced DSBs in pancreatic cancer cells. In addition, DSF alone boosted IR-induced cell cycle G2/M phase arrest and apoptosis in pancreatic cancer exposed to IR. RNA sequencing and bioinformatics analysis results suggested that DSF could trigger cell adhesion molecule (CAM) signaling, which might be involved in its function in regulating the radiosensitivity of pancreatic cancer cells. In conclusion, we suggest that DSF alone may function as a radiosensitizer for pancreatic cancer, probably by regulating IR-induced DNA damage, cell cycle arrest and apoptosis, at least partially through the CAM signaling pathway.